A new species of Tmesiphorus LeConte from northern Myanmar (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei (Zootaxa, 2022)
A new species of the pselaphine genus Tmesiphorus, T. shihongliangi sp. nov., is described and illustrated from Kachin State, North Myanmar, and is compared with and separated from allied congeners.